Pengaruh Orientasi Kewirausahaan Dan Orientasi Pasar Terhadap Kinerja Usaha UMKM Kuliner (Studi Pada UMKM Kuliner Di Wilayah Iringmulyo Kota Metro) - Jati Imantoro; Ana Septiani; Indah Puspita Sari (Jurnal Manajemen DIVERSIFIKASI, 2024)
To find out whether market orientation affects business performance. To find out whether entrepreneurial orientation and market orientation affectbusiness performance. The sample of this study was culinary MSME actors in the Iring Mulyo Area of Metro City as many as 70 respondents. Data collection using questionnaires, and data analysis using validity test, reliability test, normality test, linearity test, homogeneity test, multiple linear regression analysis, t test, f test, determination r2 test, and Statistical Hypothesis using the program (SPSS). The results showed that there is a positive influence of Entrepreneurship orientation on business performance, there is a positive influence of market orientation on business performance, and there is a positive influence of Entrepreneurship orientation and market orientation on business performance.